Empowering smallholder livestock raisers in a changing climate (Low carbon footprint approaches for the Philippines) - Goad, Marilee; Oro-Monville, Emilita; Gonsalves, Julian; Cabriole, MArie Aislinn; Ordoñez, Maita (2024)
As part of its efforts to support economically disadvantaged smallholder farmers in the Philippines, the CGIAR Climate Resilience Initiative has implemented agroforestry and climate-smart agriculture programs aimed at improving food security and nutrition. These initiatives encourage crop diversification and the introduction of small livestock, including chickens, ducks, and pigs, to enhance farmers' diets and increase their climate resilience. This program has not only improved nutrition but also generated additional income for participating farmers, with 30 households earning between PHP 4,000 and PHP 28,000 from livestock sales.